Employing ICTS: Teaching & Learning through Literature Digital Reading (LDR) - Pârlog, Aba-Carina (Linguaculture (Iași), 2024)
This article is based on a material produced under the umbrella of and funded by the Erasmus+ research project DILECTINGS (DIgital Literature Educational Competences for Teachers: Intercultural iNclusive Good-practices for Second-language learning), KA220-SCH-2CA4CF2E, coordinated by Prof. dr. Raffaella Leproni, Università degli Studi RomaTre. It was made available for training participants as part of Project Result 2, Module 5 (Creating Digital Stories: Story Writing Toolkit for Teachers) on the project platform. The current version aims to show that the use of technology in a friendly virtual environment is nowadays crucial in order to create a fertile atmosphere for planned teaching/ learning and that Literature Digital Reading (LDR) tools contribute to the development of the modern class substantially and encourage students to become autonomous users of foreign languages. Available ICTs aid educators in making better use of class time due to the impact of technology on the younger generations. Using a Web2.0 tool (Canva, Story Jumper, Storyboard That, Kahoot, Prezzi, etc.) leads to a more captivating and thought-provoking class, while teachers’ and students’ creating LDR exercises with such tools allows the latter to become digitally involved in the process of learning which makes it all the more successful and motivating. In the class material set, teachers may include a fable, a short story or just a fragment published by a classical author or a fragment created by themselves according to their instruction purpose. This digital piece of reading material focusing on a special teaching/ learning goal is quite valuable for educators focusing on grammar, particular vocabulary items or cultural knowledge. LDR lays the foundation of students’ more advanced vocabulary, greater fluency and supplementary cultural awareness. Also, as a result of the LDR process and the understanding of the underlying stratum of the digital literary work or fragment used, students may learn more about the notions of coherence and cohesion which they tend to ignore during the process of writing and which are essential for a well-written essay or a short critical text. As opposed to a traditional class, an ICT class built on LDR exercises is more rewarding because it can easily adapt to students’ and teachers’ needs and help improve final results depending on the subject or language level aimed at.